TRI NGA DEVELOPING CREATIVE VALUES ON P5 INTEGRATED THE ART & CULTURE OF SUBJECTS - Wahyuni, Sri Eko; Susanto, Moh. Rusnoto (International Journal of Engagement and Empowerment (IJE2), 2023)
The aim of this activity is to describe the teaching of TRI NGA (Understanding, Ngrasa, Nglakoni) students in developing creative values ​​through the Strengthening the Integrated Pancasila Student Profile (P5) Project with SBDP content at SDN 3 KTWN. The subjects of this activity were 22 class IV students at SDN 3 KTWN for the 2022-2023 academic year, consisting of 10 male students and 12 female students. ˚This empowerment activity uses the phenomenological method, namely a community service method that describes phenomena that occur in the field in a real and concrete way through data mining using observation, questionnaires, interviews and documentation techniques. The instruments used in this research were observation sheets, questionnaires, lists of questions, and activity documentation. The data analysis technique in this presentation is carried out using qualitative descriptive techniques referring to the Miles and Huberman analysis technique which consists of the stages of data collection, data reduction, data presentation and drawing conclusions. Project activities are carried out in five stages, namely 1) Introducing students to plastic, 2) Analyzing the conditions of the surrounding environment, 4) Analyzing the dangers of plastic waste, 3) Real action: how to overcome the plastic problem, 5) Work Title P5. The research results show that Tamansiswa TRI NGA teaching is able to develop students' creative values ​​through the Pancasila Student Profile Strengthening Project (P5) which integrates SBDP content in class IV of SDN 3 KTWN